2022
DOI: 10.3389/fphar.2022.1039022
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of natural medicines against excessive inflammation and oxidative stress in acute lung injury by regulating the Nrf2 signaling pathway

Abstract: Acute lung injury (ALI) is a common critical disease of the respiratory system that progresses into acute respiratory distress syndrome (ARDS), with high mortality, mainly related to pulmonary oxidative stress imbalance and severe inflammation. However, there are no clear and effective treatment strategies at present. Nuclear factor erythroid 2-related factor 2(Nrf2) is a transcription factor that interacts with multiple signaling pathways and regulates the activity of multiple oxidases (NOX, NOS, XO, CYP) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Flavonoids are compounds that have the capacity to disrupt the NF-κB signaling pathway engaged in regulating the inflammatory enzymes and cytokines involving interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) [ 29 ]. Recent works have shown that natural medicine such as flavonoid active ingredients can decrease inflammatory and oxidative stress and have protective effects against lung injury through the erythroid 2 related factor 2 (Nrf2) signaling pathway [ 30 , 31 ]. Activated Nrf2 is an intracellular antioxidant protective signal distributed in several organs, including the lungs, where antioxidation and detoxification cascades are routinely processed [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are compounds that have the capacity to disrupt the NF-κB signaling pathway engaged in regulating the inflammatory enzymes and cytokines involving interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) [ 29 ]. Recent works have shown that natural medicine such as flavonoid active ingredients can decrease inflammatory and oxidative stress and have protective effects against lung injury through the erythroid 2 related factor 2 (Nrf2) signaling pathway [ 30 , 31 ]. Activated Nrf2 is an intracellular antioxidant protective signal distributed in several organs, including the lungs, where antioxidation and detoxification cascades are routinely processed [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the nuclear translocation of Nrf2 is pivotal to responding to chemical or oxidative stress through its interaction with ARE ( 49 ). Ample investigations have shown that genetic ablation of Nrf2 worsens the inflammation and increases the oxidative stress in numerous disease models, including pulmonary fibrosis ( 50 ), sepsis ( 51 ), acute lung injury ( 52 ), COPD exacerbations ( 53 ), and emphysema ( 54 ). Pharmacological or genetic activation of Nrf2 decreases oxidative stress and inflammation ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7A and 7B, as low as 10 −7 M of alismol could activate Nrf2. To confirm that alismol activated Nrf2, we examined whether alismol suppressed the ubiquitination of Nrf2 to activate Nrf2, given that Nrf2 became inactivated by ubiquitination [15]. HEK 293 cells were transfected with plasmids encoding V5-tagged Nrf2, Flag-tagged Keap1, and HA-tagged ubiquitin.…”
Section: Alismol Protects Mice From Ali-associated Lung Damagementioning
confidence: 99%
“…As a countermeasure to the deleterious ROS, cells can activate nuclear factor-E2-related factor 2 (Nrf2) [10], a transcription factor that regulates the expression of NAD(P)H: quinine oxidoreductase-1 (NQO-1), heme oxygenase-1 (HO-1), and glutamyl cysteine ligase catalytic units (GCLC) [11], which are involved in removing and guarding against the harmful effects of ROS. Since studies with Nrf2 knock-out mice have shown a critical role of Nrf2 in protecting mice from ALI [12,13], Nrf2 can be another therapeutic target for treating ALI [14,15].…”
Section: Introductionmentioning
confidence: 99%